PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA REALISTIK DENGAN SETTING KOOPERATIF TIPE TPS (THINK PAIR SHARE) POKOK BAHASAN PERSEGI PANJANG DAN PERSEGI UNTUK SISWA KELAS VII SMP - Maulia, Levi Arista; Susanto, S; Suharto, S (Kadikma, 2014)
Abstract.The goal of this research aims to know the process and the result of developmental Realistic Mathematics Educatioan Instruments by think pair share setting for square and rectangle topics at seven grade junior high school. Learning instrument development model refers to four D models. The products of this research are lesson plan, student book, worksheet, and evaluation test. The products refer to the characteristic of Realistic Mathematics Education and phases of Think Pair Share. Based on the validation process try out of learning instruments, it can be concluded that the learning instrumets have satisfied of the validity, practice, and effective criteria. Key Words:Realistic Mathematics Education, Think Pair Share, square and rectangle.